IMPLEMENTASI PENDIDIKAN RAMAH ANAK DALAM PEMBENTUKAN KARAKTER SISWA KELAS RENDAH SD MUHAMMADIYAH PROGRAM KHUSUS KOTTA BARAT TAHUN PELAJARAN 2013/ 2014 - Risminawati Risminawati; Siti Nur Rofi'ah (Profesi Pendidikan Dasar, 2015)
This study aims to determine the implementation of child-friendly education in shapingthe character of low-grade elementary school students at Muhammadiyah SpecialProgramme in the academic year 2013/2014. This research is qualitative research. Thesubjects of the study were low-grade teachers and students. Research procedure includesseveral phases: pre-fi eld, phase fi eld activities, and post-fi eld.The data collection used areinterviews, observation, fi eld notes and documentation. Data is analized through descriptivequalitative: data reduction, data display and verifi cation to draw conclusions. The fi ndingsinform that the child-friendly education is done through routinity, exemplary teachers, thelearning process and the advice given to students. Constraints in the character formationare parenting, environment and the increasing of sophisticated technology. Solutionsare done through home visit, through books liaison and communication with parents. Theconclusion from this study is the implementation of child-friendly education in shapingthe character of low grade students performed in a variety of activities both inside andoutside the learning process of the learning process. Child-friendly education is done inSD Muhammadiyah Special Program Kotta West can shape the character of students.